2021
DOI: 10.3389/fmicb.2021.779988
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Bactericidal Activities of Combination Antibiotic Therapies Against Carbapenem-Resistant Klebsiella pneumoniae With Different Carbapenemases and Sequence Types

Abstract: Carbapenem-resistant Klebsiella pneumoniae (CRKP) is becoming increasingly problematic due to the limited effectiveness of new antimicrobials or other factors such as treatment cost. Thus, combination therapy remains a suitable treatment option. We aimed to evaluate the in vitro bactericidal activity of various antibiotic combinations against CRKP with different carbapenemase genotypes and sequence types (STs). Thirty-seven CRKP with various STs and carbapenemases were exposed to 11 antibiotic combinations (po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Carbapenemase genotypic characterization was performed using whole-genome sequencing as previously described [ 22 ]. In brief, genomic deoxyribonucleic acid (DNA) was extracted and purified from overnight bacterial cultures with the DNeasy blood and tissue kit (Qiagen GmbH, Hilden, Germany) according to the manufacturer’s protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Carbapenemase genotypic characterization was performed using whole-genome sequencing as previously described [ 22 ]. In brief, genomic deoxyribonucleic acid (DNA) was extracted and purified from overnight bacterial cultures with the DNeasy blood and tissue kit (Qiagen GmbH, Hilden, Germany) according to the manufacturer’s protocol.…”
Section: Methodsmentioning
confidence: 99%
“…The team has long been interested in developing individualized combination therapies -christened in vitro antibiotic combination testing -for extensively drug-resistant organisms. [85][86][87][88] It is fortuitous that in our hospital, such research is undertaken by a team including a few ASP pharmacists. The ASP pharmacist rounding with the TID physician can act as a bridge, recruiting patients with difficult-to-treat MDROs into studies (fortunately a rare occurrence).…”
Section: Looking Beyond the Current Core Strategies In Stewardshipmentioning
confidence: 99%
“…In our hospital, there is a well‐established research team led by ID‐trained pharmacists, some of whom are members of the ASP. The team has long been interested in developing individualized combination therapies ‐ christened in vitro antibiotic combination testing – for extensively drug‐resistant organisms 85–88 …”
Section: Looking Beyond the Current Core Strategies In Stewardshipmentioning
confidence: 99%
“…15 Previous studies have found that cefepime in combination with polymyxin B demonstrated bactericidal activity in 24 out of 37 isolates. 19 And FEP/AVI exhibited potency against CTX-M-15 producing Escherichia coli (E. coli) and Klebsiella pneumoniae (K. pneumoniae), 7,20 but the antibacterial activity and resistance mechanism of this combination has not been extensively studied. Therefore, this study compared the antibacterial effects of CAZ/AVI and FEP/AVI against CRKP, and explored the resistance mechanism of FEP/AVI through proteomics and metabolomics studies.…”
Section: Introductionmentioning
confidence: 99%